Health Emergency Research Preparedness: An Analysis of National Pre‑COVID Research Activity and COVID Research Output - Peter H. Kilmarx; Shirley Kyere (Annals of Global Health, 2025)
Background: Research capacity is a critical element of health emergency preparedness, but metrics are not readily available for many countries. The COVID‑19 pandemic provided an opportunity to use publicly available data to assess correlations between national pre‑pandemic research activity, pandemic research response, and other national socioeconomic characteristics. Methods: National pre‑pandemic (2018–19) research activity was defined as the average of percentile rankings of (1) the average annual number of health science publications in Scopus and (2) the average annual number of clinical trials in the International Clinical Trials Research Platform (ICTRP). National pandemic research response (2020–21) was defined as the average of percentile rankings of (1) average annual number of COVID‑19‑related publications in Scopus and (2) average annual number of COVID‑19‑related clinical trials in ICTRP. Findings: During 2018–19, the median (interquartile range [IQR]) of national annual average health science publications was 415 (108–3,398) and of clinical trials was 21 (4–273). During 2020–21, the median (IQR) of national annual average COVID‑19‑related publications was 85 (18–798) and that of COVID‑19‑related clinical trials was 1.5 (0–11). National COVID‑19‑related research output was strongly correlated with pre‑pandemic research activity (R‑squared 0.89) and much less correlated with Human Development Index (0.26), COVID‑19 case number (0.16), case rate (0.14), gross domestic product (0.11), or population (0.10). In a multivariable linear regression analysis, national pre‑COVID‑19 research activity was the only factor with substantial or statistically significant contribution to explaining variations in COVID‑19‑related research output. Interpretation: National pandemic research responses were most strongly correlated with pre‑pandemic research activity, much more so than with other country characteristics. These findings strongly support global efforts to strengthen research capacity as a critical element of preparedness for health emergencies.